PENGARUH DIGITALISASI PERPAJAKAN MELALUI SISTEM CORETAX TERHADAP EFISIENSI BIAYA KEPATUHAN PAJAK OLEH WAJIB PAJAK MENENGAH - Rangga Yuda Nugraha, Yongky (Jurnal Administrasi Profesional, 2025)
Digital transformation of tax administration through the Core Tax Administration System (Coretax) represents a strategic innovation to optimize tax compliance cost efficiency for medium-scale taxpayers in Indonesia. The digitalization phenomenon in taxation has emerged as a fundamental paradigm in fiscal system modernization aimed at reducing compliance cost burdens that have traditionally constituted structural constraints for medium-scale business entities. This research analyzes the impact of tax digitalization implementation on compliance cost efficiency using quantitative approach with quasi-experimental difference-in-difference design on 384 medium taxpayers in South Jakarta during 2019-2024 period. Research methodology adopts purposive sampling with annual turnover criteria of Rp 4.8-50 billion, measuring compliance cost components including time costs, administrative costs, and opportunity costs through secondary data extraction from DGT tax information systems and taxpayer financial reports. Data analysis employs fixed effects regression with Ordinary Least Squares estimation and robust standard error correction to address heteroscedasticity and autocorrelation in econometric models. Research findings reveal that Coretax system implementation significantly negatively affects tax compliance costs with coefficient -0.318 (p-value = 0.002), indicating 31.8% compliance cost reduction compared to baseline period. Heterogeneity analysis demonstrates efficiency variation based on digital literacy levels, with high-literacy taxpayers achieving 38.4% efficiency compared to low-literacy 22.6%. Findings confirm digitalization strategy effectiveness in achieving dual objectives of compliance enhancement and administrative efficiency with implications of Rp 4.5 billion productive resource reallocation within study population, providing empirical evidence for optimizing digital tax transformation policies.